Explicit and Implicit Inquiry Guidance for Developing Students' Scientific Investigation Practices - Zulkarnain, Muhammad Zaky; Kurniawati, Rizky Kurniawati; Muliakoswara, Muhammad Hafizh Muliakoswara; Pramadina, Shandi Gusti Pramadina; Suyana, Iyon Suyana (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Scientific investigation is a core component of physics learning, yet many students experience difficulties in formulating investigable questions, developing hypotheses, designing fair investigations, and interpreting evidence. Although inquiry-based learning has been widely adopted to address these challenges, limited evidence is available regarding how different forms of instructional guidance influence specific dimensions of scientific investigation practices. This study compared the effectiveness of explicit and implicit inquiry guidance in developing students’ Scientific Investigation Practices during Newton’s law learning. A quasi-experimental pretest–posttest design was conducted with two intact Grade X classes at a senior high school in Indonesia. Students in the explicit guidance group received direct explanation, modelling, guided practice, and feedback, whereas those in the implicit guidance group were supported through inquiry worksheets and instructional prompts without explicit procedural instruction. Students’ scientific investigation practices were assessed using parallel written assessments administered before and after the intervention. Both instructional approaches improved students’ scientific investigation practices; however, explicit inquiry guidance produced stronger overall gains, particularly in planning scientific investigations and generating scientific questions. These findings suggest that explicit procedural and epistemic scaffolding help students engage more effectively in inquiry by making the logic of scientific investigation more visible. The study provides classroom-based evidence supporting the integration of structured guidance into inquiry-oriented physics instruction.